Consumption of pomegranate juice combina- tion with exercise effect on cholinesterase ac- tivity Irisin, Dopamine level and many bio- chemical parameters in stressed women in Kir- kuk City-Iraq - al-obaidi, Wedad Mahmood Lahmood; Al-Izzi , Mohanad Hasan Mahmood; Qadir Al-Hashimi, Marwa Abd- Alsalam (International Journal of Psychosocial Rehabilitation, 2020)
The present study is designed to evaluate the effects of consumption of pomegranate juice in combination with training exercise in activity of cholinesterase , concentration of Irisin , Dopamine and many biochemical parameters (Creatine , creatine kinase –CK- , Total protein , Glutathione –GSH- ,Ceruloplasmin , Malondialdehyde –MDA- and Catalase) Seventy-eight employed women age ( 25to 45 ) BMI ( 24±4.22 kg/m2) eighteen of these women as control while others about sixty whom women suffer from daily stress plus working in house for 12-15 h/day divided five groups: Group 1:(Control group) healthy employed working without kid for 5- 7 h/day include 18 women. Group 2 –(Stressed group) employed women(have more than 2 kid) +working for 12- 15 h/day include 20 women . Group 3- (S+CEG) Stressed employed women(have more than 2 kid )+Chronic Train- ing Exercise Group (1 h/day/ 21 day#P$yChOsOcIaL@s ) include 14 women. Group 4- (S+PJG) Stressed employed women (have more than 2 kid )+ consumption Pomegranate Juice PJ include 13women.Group 5-(S+CE+PJG) Stressed employed women (have more than 2 kid )+ Chronic Training Exercise (1 h/day/ 21 days ) + PJ include 13 women.Samples were collected randomly from Kirkuk city from October 2018 to July 2019.The result of this study show positive effect for chronic exercise alone and in combination with pomegranate juice significantly increase Irisin ,Dopamine , GSH ,CP levels and CK ,CAT activities in stressed women compared with stressed women with- out treatment. While there was significant decrease in Ach E activity ,Creatine ,MDA in stressed women training exercise only or in combination with pomegranate juice compared with stressed group only .As in previous studies the protein level show no change in experimental groups and control group.